1978
DOI: 10.1073/pnas.75.5.2306
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microviscosity of membrane lipids in leukemic cells: Two possible mechanisms

Abstract: Steady-state fluorescence polarization studies with the fluorescent lipid probe 1,6-diphenyl 1,3,5-hexatriene were done to determine the degree of microviscosity of cellular membrane lipids and serum lipoproteins in human normal donors and leukemic patients. The results show a marked decrease in microviscosity of cellular membrane lipids in both intact lymphocytes and isolated cellular plasma membranes obtained from leukemic patients in clinical relapse as compared to intact lymphocytes and isolated cellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…For example, the cell membranes of leukemia and lymphoma, which have less cholesterol and more unsaturated lipid contents in the cell membranes, showed higher fluidity as compared with those of normal lymphocytes. [1][2][3][4][5] Similar findings were observed for other cancer cell membranes. [6][7][8][9][10] The membrane dynamics with higher fluidity should be a fundamental property of cancer cells and closely related to the biological features of the proliferative potential, invasive potential, and metastatic ability.…”
supporting
confidence: 61%
“…For example, the cell membranes of leukemia and lymphoma, which have less cholesterol and more unsaturated lipid contents in the cell membranes, showed higher fluidity as compared with those of normal lymphocytes. [1][2][3][4][5] Similar findings were observed for other cancer cell membranes. [6][7][8][9][10] The membrane dynamics with higher fluidity should be a fundamental property of cancer cells and closely related to the biological features of the proliferative potential, invasive potential, and metastatic ability.…”
supporting
confidence: 61%
“…Hydrophobic regions of cell membranes were labeled for 30 min at 37°C with 2 FM l,ddiphenyl-1,3,5hexatriene (DPH) in phosphate buffers of different pH, as in [20]. Labeling was also carried out with DPH-phosphate buffer solutions containing either 2.5% glutaraldehyde, or 10 mM sodium azide, or 0.2% phenylmethylsuifanyl fluoride (PMSF).…”
Section: F'luorescence Labeling and Measurementsmentioning
confidence: 99%
“…Steady-state polarization (P) measurements were done at 37°C with a MV-1 Elscint instrument, as in [20]. For the excitation of DPH, a plane polarized 365 nm band generated from a 200 W mercury arc was employed.…”
Section: F'luorescence Labeling and Measurementsmentioning
confidence: 99%
“…Based on this assumption, fluorescence polarization analysis of DPH has been extensively used, in the last few years, to analyze the dynamic structural organization of lipids in cellular membranes (9)(10)(11) and viral envelopes (12,13). These studies have independently shown that the P values of DPHlabeled lymphoid cells are markedly lower (14,15) than those of DPH-labeled enveloped viruses (12,13). Moreover, it has also been shown that hydrophobic molecules such as cholesterol (16)(17)(18)(19) and DPH (20,21) Cells.…”
mentioning
confidence: 99%
“…The degree of fluorescence polarization (P) of the DPH-labeled liposomes, viruses, and cells was determined with the aid of the Elscint MV-1 microviscosimeter as described (15,20), and the P value was recorded directly by the instrument according to the equation…”
mentioning
confidence: 99%